FUNGSI CEK FISIK KENDARAAN BERMOTOR DIKAITKAN DENGAN PERATURAN KAPOLRI NOMOR 5 TAHUN 2012 TENTANG REGISTRASI DAN IDENTIFIKASI KENDARAAN BERMOTOR DI KANTOR SAMSAT KOTA BOGOR - santo, Ikh; Suprijatna, Dadang; Gilalo, J. Jopie (DERECHTSSTAAT, 2017)
The background is  study because of their expectations and the reality is much different. The expectations of society, the function is physical check of motor vehicles in Bogor City Police Office Samsat, the service satisfactory,  work professionally, proportional and procedural, so that public services can be felt by both the performance conducted by officers Samsat, especially in the service of the physical check both new vehicles , behind the name, extension of five years, aid physical check. The service is done either to individuals, enterprises or government agencies. Whereas in fact there are officers who play in the implementation of the physical check services such motor vehicle is to prioritize services to enterprises or government agencies. This study was conducted in normative, in the implementation of this study the authors used normative juridical approach, legal or norm, and juridical sociological , legal opening up on social changes, especially Cek  Physical Function, Motor Vehicle Registration and Identification , in giving excellent service. In year 2010 there were 68.511 vehicles, the year 2011 recorded 74.459 units of vehicles,  the year 2012 there were 75.630 vehicles, the year 2013 there were 85.029 vehicles, in 2014 there were 86 343 vehicles , the analysis that there is service improvement must be balanced with the ability of human resources professionals, so that all requests relating to a physical check of vehicles or vehicle registration services can make a positive contribution to society.